Near-infrared light triggered in situ release of CO for enhanced therapy of glioblastoma - Juan Ge; Miaomiao Zuo; Qirong Wang; Zhen Li (Journal of Nanobiotechnology)
Abstract Background Photodynamic therapy (PDT) features high biocompatibility and high spatiotemporal selectivity, showing a great potential in glioblastoma (GBM) treatment. However, its application was restricted by the poor therapeutic efficacy and side effect. Results In this study, a therapeutic nanoplatform (UCNPs@Ce6/3HBQ@CM) with combination of PDT and CO therapy was constructed, in which a photoCORM and a photosensitizer were loaded onto the surface of upconversion nanoparticles (UCNPs) functioning as photon transducer. Benefitting from NIR excitation and multicolor emission of UCNPs, the penetration depth of excitation light is enhanced and meanwhile simultaneous generation of CO and ROS in tumor site can be achieved. The as-prepared nanocomposite possessed an elevated therapeutic efficiency with the assistance of CO through influencing mitochondrial respiration and depleting ATP, accompanying with the reduced inflammatory responses. By wrapping a homologous cell membrane, the nanocomposite can target GBM and accumulate in the tumor site, affording a powerful tool for precise and efficient treatment of GBM. Conclusion This therapeutic nanoplatform UCNPs@Ce6/3HBQ@CM, which combines PDT and CO therapy enables precise and efficient treatment of refractory glioblastoma.